Umbilical-spinous line: a morphological term that should be included in the anatomical terminology (Colombia Medica, 2013)
We argue the need to include in the International Anatomical Terminology the term "Umbilical-spinous line" for its importance as a morphological referent in bioscopic and surface anatomy. Also, in order to avoid using eponyms, it is suggested that the traditional term "McBurney point" be replaced by "supra spinous point" as being more descriptive of location.